2014
DOI: 10.5505/jkartaltr.2014.48568
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the children with Hand-foot-mouth disease in a two-years period

Abstract: El-ayak-ağız hastalığı, ateş ve el, ayak ve ağızda veziküler lezyonlarla seyreden bir hastalıktır. Döküntü şikayeti ile başvuran çocuk hastalarda son dönemde artış gösteren el-ayak-ağız hastalığına dikkat çekmeyi amaçladık. Gereç ve Yöntem: Yeditepe Üniversitesi Hastanesi Çocuk Sağlığı ve Hastalıkları Bölümü'ne Ocak 2011-Ocak 2013 tarihleri arasında başvurup el-ayak-ağız hastalığı tanısı alan 127 çocuk hastanın geriye dönük olarak demografik veriler, şikayetler ve fizik muayene bulguları değerlendirildi. Bulgu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
2
1
Order By: Relevance
“…In the same study, apart from the hands, feet and mouth, involvement of the knee, elbow, gluteal region and face was determined at a rate of 54.54% (7). These results were consistent with those of studies conducted abroad and in our country (2,6,9,10,13,17).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…In the same study, apart from the hands, feet and mouth, involvement of the knee, elbow, gluteal region and face was determined at a rate of 54.54% (7). These results were consistent with those of studies conducted abroad and in our country (2,6,9,10,13,17).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, it was determined that 40.4% of the children in the experimental group had fever, while none of the children in the control group had fever. In four different studies conducted in our country, the reported incidence of fever in children with hand-foot-and-mouth disease varied between 61.40% and 82.10% (6,(9)(10)(11). The incidence of fever was lower in this study.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…It exhibits a single annual rise in summer or fall in countries located at higher latitudes (Blomqvist et al 2010;Huang et al 2015;Wang et al 2017). In Turkey, individual studies showed that the frequency of HFMD rises during summer (Topkarcı 2013; Uğraş et al 2014;Yorulmaz and Onat 2017). In parallel with the previous research, in the present study, it has been observed that the majority of HFMD cases (67%) applied to our hospital during summer months.…”
Section: Discussionmentioning
confidence: 99%